Treating the musician rather than the symptom: The holistic tools employed by current practices to attend to the non-motor problems of musicians with task-specific focal dystonia - Détári, Anna (Frontiers in Psychology, 2023)
Musicians Focal Dystonia (MFD) is a task-specific movement disorder affecting highly skilled musicians. The pathophysiology is poorly understood, and the available treatments are unable to fully and reliably rehabilitate the affected skill. Recently, the exclusively neurological nature of the condition has been questioned, and additional psychological, behavioral, and psychosocial contributing factors were identified. However, very little is known about how these factors influence the recovery process, and how, if at all, they are addressed in ongoing practices. For this study, 14 practitioners with substantial experience in working with musicians with MFD were interviewed about the elements in their approach which are directed at the cognition, emotions, attitudes, and behaviors of their patients and clients. A wide variety of tools were reported in three areas: (1) creating a supportive learning environment and addressing anxiety and perfectionism, (2) using body-oriented methods to optimize the playing behaviors and (3) consciously channeling the focus of attention to guide the physical retraining exercises and establishing new habits. The study also revealed that in-depth knowledge of the instrumental technique is profitable to retrain the impaired motor patterns. Therefore, the importance of including music educators in developing new therapeutic approaches will also be highlighted.